Analysis of the Main Employment Trends at EU and Romanian Levels - Daniela Pasnicu (Journal of Economic Development, Environment and People, 2019)
Lately, the European Union has made progress in the labor market, especially in terms of employment, except in the economic crisis. The purpose of the article is to highlight the main labor market trends at European Union level, with an emphasis on employment as well as differences between Member States in the context of current challenges, namely long-term demographic trends and technological change. In this respect, two EU Member States, namely Romania and the UK, were also taken into account in order to highlight the differences between advanced and less advanced economies in terms of employment opportunities and the integration of vulnerable people on the labor market. The analysis, which emphasizes demographic change and employment, can serve as a basis for knowledge for the design of national policy instruments by emphasizing deficits, surpluses or equilibria. Trends are analysed dynamically over the 2007-2017 period, based on EUROSTAT data. The challenge for decision-makers is to increase labor force participation and to ensure that every citizen has the chance to make full use of his productive potential.